'It definitely made a difference': A grounded theory study of yoga for pregnancy and women's self-efficacy for labour. (January 2019) - Campbell, Virginia; Nolan, Mary
Abstract: Objective: To explore women's experience of attending yoga for pregnancy classes in order to generate a theory about which aspects, if any, are effective in enhancing self-efficacy for labour and birth. Design: A longitudinal grounded theory study. Methods: Semi-structured interviews were undertaken with women before they started yoga for pregnancy classes, after they had attended at least six classes, and finally, postnatally. Interview transcripts were analysed using constructive grounded theory and a self-efficacy framework. Setting: Three yoga for pregnancy teachers' classes in England. Participants: Twenty two women attending yoga for pregnancy classes. Findings: Analysis of interviews with women at three time points led to a propositional theory that yoga for pregnancy enhances women's self-efficacy for labour by building their confidence and competence through a combination of techniques. These include repeated practice of a variety of pain management strategies, use of affirming language and the telling of positive labour stories, underpinned by yoga practice to lower somatic response to stress.